2007
DOI: 10.1111/j.1600-0404.2007.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome and metabolic syndrome

Abstract: Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy. Many factors such as diabetes mellitus, hypothyroidism, hormonal replacement therapy, corticosteroid use, rheumatoid arthritis and wrist fractures may cause CTS. Metabolic syndrome includes abdominal obesity, dyslipidemia, hyperglycemia, and hypertension that may cause CTS. In this study, we aimed to evaluate the relation between CTS and metabolic syndrome. We studied 107 (96 female and 11 male) right-handed patients who had a clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 36 publications
(49 reference statements)
5
41
3
1
Order By: Relevance
“…A high prevalence of metabolic syndrome has been found in patients with CTS, but the mechanisms behind this are not fully understood [24,25]. The current hypothesis is that the metabolic syndrome, and its individual components, is important for the onset and progression of peripheral neuropathy [6], where the underlying mechanisms, including fatty deposition in nerves, extracellular protein glycation, mitochondrial dysfunction, oxidative stress and counter-regulating signaling pathways leading to inflammation, may be different in 13 type 1 and 2 diabetes [6].…”
Section: The Metabolic Syndrome In Cts and Neuropathymentioning
confidence: 99%
“…A high prevalence of metabolic syndrome has been found in patients with CTS, but the mechanisms behind this are not fully understood [24,25]. The current hypothesis is that the metabolic syndrome, and its individual components, is important for the onset and progression of peripheral neuropathy [6], where the underlying mechanisms, including fatty deposition in nerves, extracellular protein glycation, mitochondrial dysfunction, oxidative stress and counter-regulating signaling pathways leading to inflammation, may be different in 13 type 1 and 2 diabetes [6].…”
Section: The Metabolic Syndrome In Cts and Neuropathymentioning
confidence: 99%
“…It can therefore be concluded that obesity is associated with CTS, but weight loss in bariatric surgery is not sufficient to improve its repercussions in daily life. The higher prevalence of CTS in obese individuals is already well known in the literature [6][7][8][9][10][11][12][13] . Similarly, Moghtaderi et al 8 conducted a case-control study examining risk factors for CTS and demonstrated that BMI, age and anthropometric data of the wrist were higher in patients with CTS than in controls.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The most widely accepted theories for CTS ethiopathology are the mechanical and the microvascular nerve damage 2 . Many authors considered obesity as a predisposing factor [6][7][8][9][10][11][12][13] , as it may be associated to the mechanical theory when the fat tissue causes nerve root compression and raises local hydrostatic pressure 10,12 . However, microvascular insufficiency secondary to atherosclerosis, which is more common in the obese population 13 , may also play a role.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…In addition, similar to our study, median nerve parameters were worse in patients with metabolic syndrome, implying advanced disease. 16 The pathophysiology of CTS involves different mechanisms. Elevated carpal tunnel pressure is the main pathology, causing mechanical compression and local ischemia.…”
Section: 415mentioning
confidence: 99%